Deviating from the norm: Nuclear organisation in trypanosomes - Field, Mark C (Current opinion in cell biology, 2023)
At first glance the nucleus is a highly conserved organelle. Overall nuclear morphology, the octagonal nuclear pore complex, the presence of peripheral heterochromatin and the nuclear envelope appear near constant features right down to the ultrastructural level. New work is revealing significant compositional divergence within these nuclear structures and their associated functions, likely reflecting adaptations and distinct mechanisms between eukaryotic lineages and especially the trypanosomatids. While many examples of mechanistic divergence currently lack obvious functional interpretations, these studies underscore the malleability of nuclear architecture. I will discuss some recent findings highlighting these facets within trypanosomes, together with the underlying evolutionary framework and make a call for the exploration of nuclear function in non-canonical experimental organisms.
Keywords: Eukaryogenesis; molekulární evoluce; jaderný obal; Nuclear envelope; Cell Nucleus; Nuclear pore complex; Molecular evolution; Nuclear Pore; laminy; Evolution, Molecular; Nuclear Pore Complex Proteins; Nuclear architecture; Lamina; buněčné jádro; jaderná lamina; Lamins; komplex proteinů jaderného póru; Nuclear Envelope; jaderný pór; Nuclear Lamina; Trypanosomes; Trypanosoma